2022
DOI: 10.1021/acsaem.2c02698
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Nickel Arsenide Nanocrystals for Electrochemical Water Splitting

Abstract: We report a detailed study on the first colloidal synthesis of NiAs nanocrystals. By optimizing the synthesis parameters, we were able to obtain trioctylphosphine-capped NiAs nanoplatelets with an average diameter of ∼10 nm and a thickness of ca. 4 nm. We then studied the performance of such NiAs nanocrystals as electrocatalysts for electrochemical water splitting reactions, namely, acidic hydrogen evolution reaction (HER) and alkaline oxygen evolution reaction (OER). These nanocrystals were found to be the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In such cases, the place exchange mechanism also plays an important role in the active monolayer formation . The newly formed high energy surface of FeO­(OH) with random atomic arrangement leads to facile electro-kinetics and better OER performance, as depicted from the Tafel analysis. ,,, Impedance analysis and R ct data indicated further that the formation of amorphous FeO­(OH) also helps in a better charge transfer.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In such cases, the place exchange mechanism also plays an important role in the active monolayer formation . The newly formed high energy surface of FeO­(OH) with random atomic arrangement leads to facile electro-kinetics and better OER performance, as depicted from the Tafel analysis. ,,, Impedance analysis and R ct data indicated further that the formation of amorphous FeO­(OH) also helps in a better charge transfer.…”
Section: Resultsmentioning
confidence: 94%
“…65 The newly formed high energy surface of FeO(OH) with random atomic arrangement leads to facile electro-kinetics and better OER performance, as depicted from the Tafel analysis. 7,56,66,67 Impedance analysis and R ct data indicated further that the formation of amorphous FeO(OH) also helps in a better charge transfer. , where both the metals adopted octahedral geometry.…”
Section: Electrocatalytic Oermentioning
confidence: 96%
“…Metal arsenides are limited in their studies, most of which are related to III–V quantum dots (QDs) or use noncolloidal syntheses such as ball milling . Some colloidal syntheses include work by the Jaramillo group who synthesized orthorhombic CoAs and MoAs crystals and hexagonal Cu 3 As crystals, and the Manna group who did the first colloidal NiAs synthesis . The Manna group also showed that control of the standard InAs synthesis could be added by mediating the reduction with ZnCl 2 , which improved the size distribution of the product, and allowed for a ZnSe shell .…”
Section: Phase Control Of the Metal Pnictidesmentioning
confidence: 99%
“… 104 Some colloidal syntheses include work by the Jaramillo group who synthesized orthorhombic CoAs and MoAs crystals and hexagonal Cu 3 As crystals, 64 and the Manna group who did the first colloidal NiAs synthesis. 105 The Manna group also showed that control of the standard InAs synthesis could be added by mediating the reduction with ZnCl 2 , which improved the size distribution of the product, and allowed for a ZnSe shell. 106 While these studies show a diversity of metal arsenides the studies do not include any phase control.…”
Section: Phase Control Of the Metal Pnictidesmentioning
confidence: 99%
“…However, their high cost and scarcity hinder their wide practical application and have stimulated the development of new low‐cost and durable non‐noble metal materials [8–10] . Among them, non‐noble transition metal‐based catalysts (TMBCs) with high abundance and diversity, inclusive of Ni, Mn, Co, V, Fe and Mo‐based compounds have been considered as promising alternatives in various forms, such as oxides, [11] (oxy)hydroxides, [12–14] phosphides, [15–17] borides, [18] carbides, [19] nitrides, [20] arsenides, [21,22] sulfides, [23–25] and selenides and tellurides [26] . Among all the transition metal‐based materials, nickel‐based electrocatalysts have attracted more attention due to their high abundance and low cost [27–39] …”
Section: Introductionmentioning
confidence: 99%